HUBUNGAN ANTARA PENGELOLAAN, PENGENDALIAN SISA MATERIAL DENGAN BIAYA DAN WAKTU PENYELESAIAN PEMBANGUNAN GEDUNG PSIK DI UNIVERSITAS TRIBHUWANA TUNGGADEWI MALANG - ZULKIBLI, ZULKIBLI; Rasidi, Nawir; Arifianto, Andi Kristafi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
The construction project is closely related to construction materials. In the implementation of construction projects will certainly lead to the rest of the material. Waste materials sizeable appearing which one of them due to the use of materials that are less effective and efficient, so it can certainly be swelling, especially in the finance sector. Not only that, when waste materials has not be managed properly then it will have an impact on sustainability and an environmental damage around. The purpose of this research is to minimize the cost and time by way of the management and controlling of waste material, especially in the iron material of concrete, cement, sand, brick, gravel, ceramic. Data were obtained from: (1) direct observation in the field around the development projects in the form of direct counting and documentation of waste material on the ground; (2) The survey questionnaire respondents are contracting staff, among others are, field supervisors, foremen, consultants, supervisors, and workers. The results showed that: The percentage of the remaining cost of the largest material studied during the project implementation comes from Concrete steel material valued at IDR 5.4838 million, the total responses to questionnaires each type of waste material under study is the largest sand material waste by 19.68%, the percentage of remaining charge the material can not be used towards the cost of materials required field amounted to 4.9%, the percentage of the total cost of waste material to the total cost of the project amounted to 1.87% and the total results of the questionnaire in the field based on the source and cause of the largest waste material is (X3) handling factor amounting to 35.75%. Besides efforts to reduce material waste in the ground is a good material management methods. Keywords: Waste material, material management, the category of waste material.